PENGUATAN PAUD HOLISTIK INTEGRATIF DI PROVINSI RIAU - Novianti, Ria (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Most early childhood education services in Riau Province still not provided holistic, integrative service in schools. There has been no renewal of early childhood education services in PAUD institutions, and there has been no collaboration with various institutions, organizations, and other stakeholders. In addition, there is still a lack of knowledge among teachers and institutional managers in implementing holistic, integrative services in schools. This service aims to understand and strengthen Integrative Holistic service regarding education, health, nutrition, care, nurturing, protection, and welfare services for educators and institution managers. The implementation method in this service has four stages, namely, stage 1, a pretest filled in via a google form to find out the participants' knowledge before being given HI PAUD strengthening. In the second stage, namely the presentation of material regarding the Holistic Integrative service, questions, answers, and discussions. The third stage is giving assignments to participants, the fourth stage is the game, and the fifth stage is evaluation and posttest to see the participants' knowledge after being given the strengthening of HI PAUD. This service activity provides reinforcement and new expertise to participants in Integrative Holistic services in early childhood education schools. This can be seen from the reactions and enthusiasm of the participants in this Holistic Integrative PAUD strengthening activity.